KINEMATIC MODELLING OF STEWART PLATFORM SIMULATOR USING LINEAR ACTUATOR - ARTWODINI MUQTADIROH (NIM: 23207142), FEBY
Stewart Platform is a robot manipulator with six degrees of freedom designed using the arm that can move independently, where the length of the arm can be changed to direct the position and orientation of the platform. In that way Stewart Platform can perform translation and rotation movement of each axis in the x, y, and z. Stewart Platform Simulator is a special Stewart platform which six arms and concentrate on two areas: base as a fixed body and upper platform as a motion body. In the development of Simulator Stewart Platform is used hexagon at both the base and upper platform. However, the solutions used in the calculation is solved by the triangle on the upper platform. This method is used to obtain the approach value of hexagon upper platform. This is done to simplify the calculation.